Refractive Errors in Children of 11 to 16 Years of Age Group attending Eye OPD at Hayatabad Medical Complex Peshawar - Naveed Ahmad Mohmand, Rozina Shahadat Khan, Abid Ullah, Abid Alam (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Children of school age are susceptible to refractive error, which has a significant negative influence on lowering the learning capacity and educational potential. Aim: To estimate the frequency of different types of refractive erors in children, age group 11 to 16 year, visiting eye OPD H.M.C Peshawar. Study Design: Cross sectional descriptive study. Place and duration of study: Study has been conducted at Eye OPD of H.M.C Peshawar in three months duration. Methods: A total of 308 patients fulfilling the inclusion criterion were examined for Visual acuity. Distance visual acuity was measured both monocularly and binocularly by using a Snellen E chart at a distance of 6 meter. After refraction, best corrected visual acuity was assessed and recorded. Refractive status was recorded according to the criterion. Results: A total of 308 subjects were examined, out of which 73 (23%) were having Ammetropia i.e. having refractive error. Among 73 refractive error children 27 (36.98 %) were having Myopia and 24 (32.87%) were having Hyperopia and 22 (30.13%) were Astigmatic. It was found that male were more affected than females, having frequency of 63% and 36.98% respectively. Conclusion: Refractive error can no longer be ignored as a target for urgent action. The world must make every effort to meet the goals of VISION 2020. A child’s whole life may get ruined just because of uncorrected or inappropriately corrected Refractive error. There is dire need of public awareness regarding refractive errors and availability of services. The results show a great burden of refractive error patients on the hospital, so the facilities of the refractive services need to be increased. Keywords: Refractive error, visual acquity, Ammetropia, Hyperopia, Myopia